Analysis of the Suitability of Clove Plants in Pelabuhan Ratu Sub-District - Christian, Yoga Alfa; Manessa, Masita Dwi Mandini; Setiadi, Hafid (Jurnal Pendidikan Geografi Undiksha, 2024)
Indonesia is the largest clove-producing country in the world, this is because cloves are native plants from Indonesia which are also supported by natural conditions, climate, and topography. In Sukabumi Regency, cloves are the main production center in West Java. This study uses the scoring method by overlaying the data used. The data used in this study are rainfall data, soil type data, slope data, and altitude data. The results of this study found that the area for the "very suitable" class is quite dominant when compared to the "suitable" and "less suitable" class. the "less suitable" class has an area of 12.79 Km2 with a percentage of 13.81%, then for the "suitable" class it has an area of 29.95 Km2 with a percentage of 32.33%, and the "very suitable" class has an area of 49.91 Km2 with a percentage of 53.86%.